PENGARUH KECERDASAN EMOSIONAL TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA KELAS IV SEKOLAH DASAR ISLAM BABUSSALAM DURENAN KABUPATEN TRENGGALEK TAHUN AJARAN 2017/2018 - Muhammad Farhan Faizi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2018)
Mathematics is one of compulsory science for all human beings. However, this science is often a scourge for students so that the motivation of students to this science is low. Emotional intelligence is one of the factors that influence the high intrinsic motivation that the learners have. From the exposure, the researchers took the formulation of the problem "Is there any influence of emotional intelligence on the motivation (intrinsic) learning mathematics fourth grade students Islamic Elementary School Babussalam Durenan?". This research uses quantitative research with survey method on fourth grade students of SDI Babussalam. In collecting data using questionnaire in the form of questionnaire.Result of t analysis (tcount) 6,999> ttable 2.032 at 5% significant level with df = N - k = 36 - 2 = 34 then alternative hypothesis accepted which mean existence of influence of signivikan given by emotional intelligence to motivation learn student of fourth grade Islamic Elementary School Babussalam Pandean Durenan Sub-district of Tenggalek Regency. In the activity of teaching and learning, there should be special attention to the development of intellectual intelligence and social intelligence of children. Keywords: Emotional Intelligence, Motivational Learning Mathematics.